121k views
0 votes
identify how many terms will be in the expanded form of a polynomial equivalent to the following expression. (−6m–n)2

User AsafK
by
5.8k points

1 Answer

4 votes

Answer:

There are three terms in the expanded form of the given polynomial expression
(-6m-n)^2 equivalent to the expression
36m^2+12mn+n^2

Therefore
(-6m-n)^2=36m^2+12mn+n^2

Explanation:

Given expression is
(-6m-n)^2

To simplify the given expression as below:


(-6m-n)^2


=((-6m)+(-n))^2

(Using the property
(a+b)^2=a^2+2ab+b^2)

Here a=-6m and b=-n


=(-6m)^2+2(-6m)(-n)+(-n)^2


=6^2.m^2+12mn+n^2


=36m^2+12mn+n^2


(-6m-n)^2=36m^2+12mn+n^2

Therefore
(-6m-n)^2=36m^2+12mn+n^2

There are three terms in the expanded form of the given polynomial expression
(-6m-n)^2 equivalent to the expression
36m^2+12mn+n^2

User Adonike
by
5.0k points